Heterogeneity of avian infectious bronchitis virus population - Ye. V. Ovchinnikova; L. O. Scherbakova; S. N. Kolosov; A. N. Andriyasova; N. G. Zinyakov; Z. B. Nikonova; A. A. Kozlov; P. B. Akshalova; D. A. Altunin; D. B. Andreychuk (Ветеринария сегодня)
Avian infectious bronchitis is one of the most common viral infections causing enormous economic losses in the global poultry industry. Due to the lack of mechanisms to correct errors during genome replication, the virus can quickly mutate and generate new strains. This is facilitated by widespread use of live vaccines, simultaneous circulation of field viruses belonging to different serotypes in one flock and rapid spread of the virus. Previous studies of avian infectious bronchitis virus strains and isolates identified in the Russian Federation poultry farms showed that 50% of samples tested positive for the 4-91, D274, H-120, Ma5 vaccine strains, and the other half of samples tested positive for the field viruses belonging to eight GI genetic lineages, while the G1-19 (QX) lineage was dominant. The paper presents identification and genotyping results of the avian infectious bronchitis virus in one of the poultry farms in the Saratov Oblast (the Russian Federation) in 2018–2019. The samples of internal organs and blood, as well as oropharyngeal and cloacal swabs were taken from chicks and layers of different ages in the parent and replacement flocks. The vaccine strain, GI-19 field isolates and variant isolates that do not belong to any of the known genetic lineages were detected. Analysis of test results within a two-year period showed that it is important to study samples taken from birds of different ages. The virus undergoes modification and adaptation inducing new genetic forms by infecting several poultry generations, due to which the heterogeneity of the virus population is observed not only in the poultry farm as a whole or in a separate department, but also within one organism. The identified isolates showed tropism for the tissues of intestine, reproductive organs, and, in rare cases, trachea and lungs. The data obtained indicate that, despite the vaccination used, a genetically diverse population of the infectious bronchitis virus circulates in the poultry farm, while the infection may not manifest itself at an early age, but may affect the flock productivity in the future due to pathological changes in the reproductive organs of laying chickens.